IMPLEMENTATION OF POEE (PREDICT OBSERVE EXPLAIN EXPLORE) LEARNING METHOD TO INCREASE STUDENTS’ UNDERSTANDING CONCEPT ON KINETIC THEORY OF GASES IN GRADE XI OF SMAN 1 KRIAN - USWATUL ISNA, BETHARI (Inovasi Pendidikan Fisika, 2017)
The goals of this research were to describe the practicality POEE learning method process to increase students’ understanding concept in term of teacher’s activities treatment and students’ activities treatment during the POEE learning process, and to describe the effectiveness of POEE learning method to increase students’ understanding concept in term of significance of differences in pretest and posttest score, enhancement of understanding concept and students’ responses after POEE learning method has been done. This research was pre experimental by one group pretest posttest design. The sample of this research was determined by ensure that the population normally distributed and homogenous ability first, so it obtained grade XI MIA 1 of SMAN 1 Krian as the sample. The results of the research indicate that POEE learning method can be performed and implemented very well. While using the POEE learning method, Students could perform noticebly very well. The result explain that POEE learning method could be implemented and successfully increased, students’ activities when they were learned was categorized by very good. There are significant differences in pretest and posttest values so, students’ understanding concept could be increased by the average enhancement 0,6 and its categorized as very good. Students’ response of POEE learning method had range 76%-90% by good until very good as the criteria. Based on that result, it showed that implementation of POEE learning method could increase students’ understanding concept. Keywords: POEE, understanding concept